Incidence of Anemia among Urban and Rural High School Students in Bone Regency - Alam, Syamsul; Ibrahim, Irviani Anwar; Syarfaini, Syarfaini; Muthmainnah, Muthmainnah (Public Health Science & Religion, 2024)
Background: Anemia is a level of hemoglobin (Hb) in the blood that is below normal. In the world there are 40-88% of adolescents (10-19 years) experiencing anemia with a frequency of 26.2% in Indonesia, consisting of 59% of men and 49.1% of women. This study aims to determine the description of the incidence of anemia in rural high school students and urban high school students in Bone Regency, South Sulawesi in 2022. Methods. The type of research used is quantitative observational with an analytic observational approach with a cross sectional design. The population in this study were all female students in urban and rural areas, namely SMA 1 Bone and SMA 21 Bone with a total sample of 83 people which is equivalent to the number of samples in rural areas. The sampling technique used is non-random sampling and total sampling. Results. The results of this study indicate that there is a difference between the incidence of anemia in rural high school students and urban high school students in Bone district with an Asymp value. Sig. (2-tailed) of 0.026 <0.05. Adolescents have the potential to experience anemia because their lifestyle and consumption patterns vary due to growth and development. Conclusion. Terdapat perbedaan kejadian anemia dan status gizi pada siswi di perkotaan dan pedesaan. Tidak terdapat perbedaan pola menstruasi dan pola konsumsi inhibitor zat besi pada siswi di perkotaan dan pedesaan.